Flick Flack Training Tool for Beginner Athletes PERSANI Medan - Novita Novita; Yasmine Nadia Khairunisa (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Gymnastics is a body exercise on the floor or on a device designed to increase endurance, strength, flexibility, agility, coordination and self-control. One of them is floor exercise, this exercise also has various kinds of movements that are not easy to do, for example, the movement flick flack. Beginner athletes in PERSANI, Medan City have not mastered the movement properly flick flack due to limited tools and costs from PERSANI so that the coach has to innovate with existing tools. The population in this study were 9 Siahaanathletes Gymnastic Club, 5 Windy's Gymnastic Clubathletes, 2athletesathlete Star Kids Gymnastic Club and 1 QA Gymnastic Club in 2020. The Training tool was flick flack validated first by 9 experts, 3 experts in in sports, 3 experts in the field of equipment / media, 3 experts in the field of coaches, where the average percentage value of validity is 81.8%, thus according to the experts they get the "Good / Feasible" category. The method used is the method of development research (Research and Development / R & D). The results of the small group trial involved 14 athletes, 9 Siahaanathletes Gymnastic Club and 5athletes Wendy's Gymnastic Club  that the development of the training tool flick flack in this study can be concluded that it meets the criteria to be continued in large group trials. The results of the large group trial involved 17 athletes, 9 Siahaan Gymnastic Clubathletes, 5 Windy's Gymnastic Club, 2 athletes. Star Kids Gymnastic Club and 1athlete QA Gymnastic Club concluded that they met the criteria to be used in helping training flick flack. From the results of the validation tool, test a small group and large group trial can be concluded that the tools exercise flick flack is needed in practice flick.